A Homeowner’s Guide to the Living Shoreline Permit Exemption Part 2: United States Army Corps of Engineers - Savanna C. Barry; Sara Martin; Eric Sparks (EDIS)
Living shorelines are coastal shoreline stabilization interventions that rely on natural elements such as native vegetation and oyster reefs to protect property. The US Army Corps of Engineers, among other entities, regulates the placement of living shorelines through a permitting process to ensure project activities do not conflict with the public interest. In this 9-page guide, authors Savanna Barry, Sara Martin, and Eric Sparks provide you with example text for each application section that you can adapt to your needs to assist you in filling out the permit application. Published by the UF/IFAS Florida Sea Grant College Program. http://edis.ifas.ufl.edu/sg189